The tradability of banking services : impact and implications - Baark, Erik.; United Nations Conference on Trade and Development (Geneva : United Nations, 1994)
This book examines the tradability of banking products, particularly as regards its technical feasibility and the implications of this for both banking enterprises and national economies, including particularly, developing countries.
"ST/CTC/168."
"UNCTAD/DTCI/14"--P. [4] of cover.
"United Nations publication. Sales no. E.94.II.A12"--P. [4] of cover.
"Based on a research report prepared by Erik Baark ... [et al.]"--P. iv.
Includes bibliographical references.
rua 31/08/16
Keywords: Financial services industry; Financial services industry - Communication systems; Banks and banking - Computer networks; Banks and banking - Communication systems; Electronic funds transfers